2006
DOI: 10.1086/507340
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of the 23‐Valent Pneumococcal Polysaccharide Vaccine in the Elderly Population: The EVAN‐65 Study

Abstract: Background. The 23-valent polysaccharide pneumococcal vaccine (PPV) is currently recommended for elderly persons and persons who are at high risk of infection. However, the effectiveness of the 23-valent PPV remains controversial. We assessed the effectiveness of this vaccine in older adults.Methods. A prospective cohort study was conducted from January 2002 through April 2005; it included all community-dwelling individuals aged у65 years who were assigned to 1 of 8 primary health care centers in Tarragona, Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
0
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(127 citation statements)
references
References 29 publications
8
110
0
9
Order By: Relevance
“…[23][24][25] Additionally, we observed significant decreases in pneumococcal disease. Though the decline in invasive pneumococcal disease was at the boundary of statistical significance (p=0.05), Rhode Island went from having nearly 20 more cases of invasive disease per year than the overall rate for the United States, to having a similar rate in the post-intervention period.…”
Section: Discussionsupporting
confidence: 55%
“…[23][24][25] Additionally, we observed significant decreases in pneumococcal disease. Though the decline in invasive pneumococcal disease was at the boundary of statistical significance (p=0.05), Rhode Island went from having nearly 20 more cases of invasive disease per year than the overall rate for the United States, to having a similar rate in the post-intervention period.…”
Section: Discussionsupporting
confidence: 55%
“…For that reason, we included only studies in which important confounders (at least age and comorbidities) were recorded and taken into account in an adjusted statistical analysis. Three registry-based cohort studies [43,44,46], 3 matched case-control studies [47][48][49], and 4 "case-case studies" using the Broome method [21,[50][51][52] fulfilled this condition. Efficacy against PP was also investigated in a study with a similar case-case design, in which pneumonia cases caused by other pathogens or with no identified pathogen were used as the control group [53].…”
Section: Ppsv23mentioning
confidence: 94%
“…Indeed, the 37 Maruyama, 2010 (64% against pneumococcal pneumonia and 45% against all cap in nursing home residents); 55 Huss, 2009 (11% in elderly and chronically ill patients against all cap from 11 RcT but high heterogeneity) 54 Vaccine effectiveness …”
Section: Model Specification and Parameters Used For The Analysismentioning
confidence: 99%
“…19 Using the same calculation as used by Jackson et al 5 we obtained a total NBPP incidence of 706/100,000. Vila-Corcoles et al 37 reported an incidence of hospitalized pneumonia in Spain of 1,048/100,000 in elderly (65+) that gave a total NBPP incidence rate of 987/100,000. The study from Ament et al 19 was used in the present analysis because it represents the data of five different countries.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%